2022
DOI: 10.3390/v14061177
|View full text |Cite
|
Sign up to set email alerts
|

Omicron Sub-Lineages (BA.1.1.529 + BA.*) Current Status in Ecuador

Abstract: The Omicron variant of SARS-CoV-2 is the latest pandemic lineage causing COVID-19. Despite having a vaccination rate ≥85%, Ecuador recorded a high incidence of Omicron from December 2021 to March 2022. Since Omicron emerged, it has evolved into multiple sub-lineages with distinct prevalence in different regions. In this work, we use all Omicron sequences from Ecuador available at GISAID until March 2022 and the software Nextclade and Pangolin to identify which lineages circulate in this country. We detected 12… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Omicron's BA.1 lineage and its sub‐lineages corresponded to 42.8% of the sequenced genomes (145 genomes) in the present study (with emphasis on BA.1.14 and BA.1.14.1 sub‐lineages). The sub‐lineage BA.1.14 was widely reported in different parts of the world in the first half of 2021, being evidenced in about 82 countries with varied prevalence 26–28 . In Brazil, the distribution of these sub‐lineages remained constant throughout the first half of 2021, with the same trend in the number of sequenced genomes in the different geographic regions of the country 29,30 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Omicron's BA.1 lineage and its sub‐lineages corresponded to 42.8% of the sequenced genomes (145 genomes) in the present study (with emphasis on BA.1.14 and BA.1.14.1 sub‐lineages). The sub‐lineage BA.1.14 was widely reported in different parts of the world in the first half of 2021, being evidenced in about 82 countries with varied prevalence 26–28 . In Brazil, the distribution of these sub‐lineages remained constant throughout the first half of 2021, with the same trend in the number of sequenced genomes in the different geographic regions of the country 29,30 .…”
Section: Discussionmentioning
confidence: 93%
“…The new variant of SARS-CoV-2 quickly crossed international borders and by December 9, 2021, it had already been reported in 57 countries. 19,20 In Brazil, the Omicron variant was introduced in mid-December 2021, and by the end of [26][27][28] In Brazil, the distribution of these sublineages remained constant throughout the first half of 2021, with the same trend in the number of sequenced genomes in the different geographic regions of the country. 29,30 Study carried out between October 2021 and April 2022 with genomes from all over Brazil, showed the BA.1, BA.1.1 and BA.1.14.1 sub-lineages as the most prevalent and pointed out that Omicron was imported mainly by the state of São Paulo, which in turn dispersed the lineages to other states and regions of the country.…”
Section: Discussionmentioning
confidence: 99%
“…The studies are ordered based on the earliest date in each study. Omicron Study Country Dates BA.1 BA.2 Omicron Delta (or other variant) Cedro-Tanda et al 38 Mexico November 16, 2021 – November 21, 2021 2% 98% December 13, 2021 – December 19, 2021 65% 35% December 27, 2021 – December 31, 2021 88% 12% Mella-Torres et al 75 Chile November 29, 2021 – January 24, 2022 B.1.1529 (534/588) 90.5% 9.1%(54/588) Alpha (B.1.1.7) 0.2% (1/588) Gamma (P.1) 0.2% (1/588) Carrazco-Montalvo et al 56 Ecuador December 12, 2021 – December 18, 2021 50% (33/66) 50% (33/66) De Souza et al 25 …”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, the prevalence of the Omicron variant increased from 0.4% between December 2021–2022 (n = 241) 25 to 85% between February and March 2022 (n = 67) 64 while in Ecuador the prevalence was 50% in December 2021 (n = 66). 56 Only one study reported the prevalence of the Omicron variant in Chile as 90.8% between November 2021 and January 2022 ( Figure 3(a) ). Ranzani et al, 79 reported the increase in the prevalence of Omicron in Brazil from 1% (September – December 2021) to 100% (December 2021-April 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation